SUCCESSFUL COMMUNICATIONS AS AN ELEMENT OF EFFECTIVE MANAGEMENT OF EMERGENCY SITUATIONS - Ivetić, Zorana; Tošić, Jovanka; Miletić, Ljiljana (Poslovna ekonomija, 2023)
Although they are an integral part of human history, natural disasters have become more frequent and more devastating. The devastating effects of natural disasters, as well as technical-technological accidents and other social conflicts, lead to emergency situations. An emergency situation is defined as a situation when the risks and threats or consequences of disasters and other events are of such scope and intensity that their occurrence or consequences cannot be prevented or eliminated by the regular action of competent services and authorities. Communication is important for the successful management of an emergency situation. It is necessary to use all available communication channels so that key messages reach the public as quickly and efficiently as possible. The use of new technologies and media is becoming an indispensable means of communication in emergency situations. The role of state bodies, institutions and the media are to provide timely information about the necessary measures that need to be taken, as well as the transmission of key messages to the public. For the communication process to be successful, it must contain elements such as trust, honesty, transparency, reliability and accountability.
Keywords: emergency situation; communication; messages; communications channels; communications tools